Mailing en la Cooperativa de Ahorro y Crédito Señor del |Árbol en las agencias pertenecientes a la provincia de Cotopaxi, año 2023. - Bautista Caisaluisa, Ana María (2023)
The proper management and execution of Mailing campaigns emerge as a key resource for institutions, by establishing a crucial connection with customers and enhancing data management. The central objective of this research was to propose the use of Mailing as a communication strategy in the Señor del Árbol Savings and Credit Cooperative, whose agencies are located in the province of Cotopaxi. In the current context, email has become an integral repository of information, enriching its communicative value. The methodology adopted was framed in a descriptive investigation with a quantitative approach which serves to carry out a statistical analysis of the sample, using the survey as a technique and the questionnaire itself as an instrument, which was designed to capture perceptions and communication needs, generating revealing results. It is concluded that the use of mailing has proven to be a valuable and effective tool in the field of communication and marketing, adapting to the changing needs of organizations and users, becoming a versatile way to reach specific audiences in an efficient way. fast and direct. This is how, through this study, he underlines the importance of Mailing as a communicative resource in a Savings and Credit Cooperative. The correct implementation of this strategy can generate substantial benefits, and the tactics outlined in the action plan offer a concrete approach to strengthen communication with customers and consolidate the relationship with the Cooperative.